Karakter Visual pada Motif Ornamen Tegel Kunci Yogyakarta - Martino Dwi Nugroho (Ornamen, 2010)
Tegel is the floor covering material having the appropriate char  acteristics dengai cool tropical climate, strong, and durable. One of the tiles companies that still survive in Yogyakarta and has a long history is a Tegel Kunci company whose products have unique character. Based on the analysis can be seen that most of the motifs are using a variety of ornamental from Europe, especially the Gothic-style ornament. In addition to European decorative ornaments also widely used Islam or the style of "arabesque", especially in geometric motifs. Motifs used  are plant motifs, geometric, and geometric mixture of plant and animal motifs. Plant motifs entirely a result of both in the stylized flowers, leaves and stems. The form used is the interest that many roses, lilies, lily, and tulip. The plant leaf using a stylized three-leaf clover, oak leaves, and there is a stylized form of the stem of the plant tendrils.  Ornamental pattern geometry in addition to having a visual function,